STUDI PERBANDINGAN KELEMBAGAAN NEGARA ANTARA INDONESIA DENGAN THALAND (PERBANDINGAN KOMISI YUDISIAL DENGAN JUDICIAL COMMISSION) DALAM RANGKA MEMPERKUAT KOMISI YUDISIAL DI INDONESIA - Adisti, Evi Lidia Tri; Firdaus, Emilda; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The Judicial Commission is an organ of a State institution within the scope of judicial power, but theJudicial Commission is not an institution or organ that carries out judicial power such as the ConstitutionalCourt and the Supreme Court. In the constitutional law, the term comparative law with the termComporative method (comparison) is to compare two objects or more investigations namely similarities anddifferences that show the true nature of the two objects being compared. By comparing the constitutions ofeach country and in the context of looking for universal values regarding KY, and to find similarities ordifferences as ingredients for comparison, this is expected to be able to contribute to the existence of KY inthe constitutional system in Indonesia.The purpose of this thesis is; first, to know the General Principles in Comparison of JudicialCommission in Indonesia with the Judicial Commission in Thailand. Second, to find out the comparison ofthe Judicial Commission in Indonesia with the Judicial Commission in Thailand, in order to strengthen theJudicial Commission in Indonesia. The type of research that the author uses is the type of Normative legalresearch, the type of Normative Legal Research is a study that discusses the principles of law, legalsystematics, the extent of legal synchronization, legal history and legal comparison. The theoretical basisused is the theory of the rule of law, the theory of state institutions, the theory of the limitation of power.From the results of the study, the two main things that can be concluded Judicial Commission is thefirst, a State institution formed based on a constitution whose arrangements are within the judicial powerregulation. KY provisions are regulated in article 24B paragraph (1) of the 1945 Constitution. Second, thebasis of the arrangement between the Indonesian Judicial Commission and the Thai Judicial Commissionare both located within the Constitution of each State and located within the judicial institution.Based on this, Indonesia should involve KY in the formation of an ethics council. In order for thejudicial commission to carry out the mandate mandate as stipulated in article 24B of the 1945 Constitution,it states that KY is independent, and has the authority to maintain and uphold the honor, dignity, andbehavior of judges.Keywords: State institutions, judicial power, Judicial Commission.